2011
DOI: 10.1111/j.1399-0039.2011.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble human leukocyte antigen‐G expression in hepatitis B virus infection and hepatocellular carcinoma

Abstract: We investigated soluble human leukocyte antigen-G (sHLA-G) expression according to the phases of hepatitis B virus (HBV) infections and hepatocellular carcinoma (HCC). A total of 267 sera from anti-HBs positive healthy individuals (n = 50), chronic HBV carriers (n = 45), as well as patients with active hepatitis B (n = 46), liver cirrhosis (LC, n = 46) and early stage HCC (n = 80) were collected and assayed for sHLA-G. Relationships between sHLA-G levels and clinicopathologic parameters including HCC stages, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…7 Soluble HLA-G isoforms can form homodimers (78-kDa) through the generation of Cys42-Cys42 disulfide bond. 8 Several reports were interested into the study of HLA-G implication in the pathogenesis of HBV infection, [9][10][11] whereas other studies focused only on the total sHLA-G levels and its correlation to clinical outcomes of HBV infection. In this study, we evaluated sHLA-G serum levels as well as its dimerization in patients with chronic HBV infections, spontaneous resolvers and healthy controls (HC).…”
Section: Discussionmentioning
confidence: 99%
“…7 Soluble HLA-G isoforms can form homodimers (78-kDa) through the generation of Cys42-Cys42 disulfide bond. 8 Several reports were interested into the study of HLA-G implication in the pathogenesis of HBV infection, [9][10][11] whereas other studies focused only on the total sHLA-G levels and its correlation to clinical outcomes of HBV infection. In this study, we evaluated sHLA-G serum levels as well as its dimerization in patients with chronic HBV infections, spontaneous resolvers and healthy controls (HC).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al detected higher levels of sHLA-G in patients with active HBV and HCC than healthy controls. Their results also showed increased levels of sHLA-G in early stages of HBV-mediated HCC [89]. However, in a recent study, we observed no correlation between HLA-G expression and the presence of HBV genome in HCC tissues [48].…”
Section: (41)mentioning
confidence: 64%
“…Moreover, the concentrations of sHLA‐G were higher in the patients with HCC than in those with liver cirrhosis or active hepatitis B, suggesting that serum sHLA‐G concentrations may be associated with the different phases of hepatitis B infection. They did not find any association between sHLA‐G concentrations and HCC stage, number of tumors, pathologic grade and presence of vascular invasion . Other study, examining 15 SNPs in the nonclassical class I alleles, found that the SNPs rs17875380, rs41557518, rs114465251, and rs115492845 were associated with susceptibility to chronic hepatitis B infection or HCC, and HLA‐F*01:04 , HLA‐G*01:05N , and HLA‐E*01:01 were associated with hepatitis B or hepatitis B with HCC, concluding that these polymorphisms may play an important role in immune surveillance of hepatitis B and HCC, possibly leading to immune responses to virus or cancer cells .…”
Section: Discussionmentioning
confidence: 96%